Nexus between Financial Leverage and Board Independence of Public-Listed Firms: Is There Any Stylised Fact? - Kok, Wai-Cheng; Lau, Wee-Yeap; Yip, Tien-Ming (Journal of Indonesian Economy and Business, 2023)
Introduction/Main Objectives: This paper examines the relationship between financial leverage and board independence for firms listed on the Malaysian stock exchange. Research Methods: This research is conducted using sample of 265 non-financial firms listed on Bursa Malaysia from 2014 to 2018. Finding/Results: Our results show: first, board independence is essential in reducing firm leverage. However, board independence does not affect all firms equally. In particular, board independence has insignificant influences on the financial leverage of young or small firms. In contrast, the financial leverage of old or large firms is negatively associated with board independence. Second, the financial leverage of firms with low profitability is adversely affected by the presence of independent directors. However, the negative impact diminishes as the firms’ profitability increases. Conclusion: These results indicate the importance of having independent directors for old, large, or low-profitability firms to reduce their financial leverage. These findings contribute to the stylised facts of the nexus between financial leverage and board independence.